Retrospective exam of a legal historian after Bolonia´s process - Clavero, Bartolomé (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The article puts forward a critical review of the different curriculums that the Spanish university has known between the second half of the 20th century and the first decades of the 21st century. Some of its deficiencies are pointed out and the author proposes moving towards a model where constitution will be the core that articulates law studies, both public and private. In this model, propaedeutic subjects would be located in postgraduate and/or specialization studies.
Keywords: Legal education; law studies; legal curriculum; Bolonia process; university